Value of preoperative luteinizing hormone before laparoscopic ovarian drilling in polycystic ovarian syndrome with clomiphene resistance - Ayman Abd-Elhakim Abd-Elghany Ibrahim; Mahmoud Elsayed Abd-Elrazek Mohammed Donia; Wael M Hosam El-Din (Journal of Medicine in Scientific Research, 2018)
Background Polycystic ovary syndrome (PCOS) is considered the most common endocrine-metabolic disorder in women in reproductive age with decreased rates of ovulation and metabolic alterations, with resulting subfertility. Clomiphene citrate (CC) is a widely used first-line treatment for infertile women with PCOS, but approximately 20% of patients have been shown to be CC resistant. Laparoscopic ovarian drilling (LOD) is a treatment option for infertile women with CC resistant PCOS. The use of a clinical biomarker such as luteinizing hormone (LH) to identify the subgroup of patients who are sensitive to LOD may be an important and consistent way to increase the efficiency of this treatment. Objective To evaluate the efficiency of the preoperative LH serum level assay to predict fertility improvement of the LOD in CC resistant PCOS. Patients and methods A prospective interventional clinical study was carried out on 44 patients with PCOS diagnosed via clinical, laboratory, and sonographic criteria. All cases had failed to respond to CC 150 mg/day/for 5 days of 6 successive cycles. Before LOD, the mean serum levels of follicle stimulating hormone, LH, and LH/follicle stimulating hormone ratio were estimated. LOD was done using a probe of endocoagulation to produce a maximum of four punctures for each ovary with 4-mm depth. All patients were followed up for 6 months postoperatively after the LOD procedure to evaluate the effect of the procedure on the spontaneous ovarian follicular growth (primary outcome), and the secondary outcomes of the occurrence of the ovulation, gain of conception, and clinical regulation of the menstrual abnormalities. Results LOD was an efficient treatment modality to achieve good ovarian follicular growth response in 34 (77.2%) cases. The preoperative serum LH cutoff level of 8.35 mIU/ml was a good predictor of LOD follicular response with 89% sensitivity and 83% specificity. Preoperative serum LH level of greater than or equal to 8.35 mIU/ml was a good prognostic marker for the satisfactory follicular response with normalization of menstrual rhythm in 30 (68.2%) cases and ovulation with subsequent pregnancy in 26 (59%) cases within 6 months of follow-up period. Conclusion Preoperative LH greater than or equal to 8.35 mIU/ml may be an efficient predictor and prognostic factor for LOD outcomes of improved menstrual pattern, spontaneous follicular growth, ovulation, and increased pregnancy rate in patients with PCOS with clomiphene resistance.